The Role Of Government Accounting Standards On The Quality Of Regional Financial Reports - Sebrina Handayani; Sarah Vika Sabrina; Mutiara Ramadani; Vebby Anggraeni Novita Sari Purba; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine and analyze the role of Government Accounting Standards in improving the quality of regional financial reports. This study uses a descriptive approach with a literature review method. Based on the results of the analysis from various sources, it is concluded that the implementation of Government Accounting Standards consistently contributes significantly to the quality of financial reports. This finding is supported by research showing that factors such as human resource competence and accounting information systems play an important role in Government Accounting Standards implementation. However, there are challenges in implementation, such as limited infrastructure and lack of training, which can hinder the quality of financial reports. Thus, although Government Accounting Standards provides a clear framework, its effectiveness is highly dependent on policy support and capacity building at the regional level.